Natural Disasters : Mitigating Impact, Managing Risks - Laframboise, Nicole (IMF Working Papers; Working Paper ;, 2012)
This paper reviews the literature on the macroeconomic impact of natural disasters and presents the IMF's role in assisting countries coping with natural catastrophes. Focusing on seven country cases, the paper describes the emergency financing, policy support, and technical assistance provided by the Fund to help governments put together a policy response or build a macro framework to lay the foundation for recovery and/or unlock other external financing. The literature and experience suggests there are ways to strengthen policy frameworks to increase resilience to natural disaster shocks, including identifying the risks and probability of natural disasters and integrating them more explicitly into macro frame-works, increasing flexibility within fiscal frameworks, and improving coordination amongst international partners ex post and ex ante.